Analysis of binomial sampling data for estimating thrips densities on ornamental plants - Worner, S.P.; Chapman, R.B. (New Zealand Plant Protection, 2000)
Compared with standard sampling methods binomial sampling reduces the time required to assess densities of pest species Such sampling is promoted as a practical procedure for use by nonspecialists A leaf sampling method was used to estimate the density of greenhouse thrips on a viburnum hedge at different stages of thrips population growth Three methods were used to relate the proportion of leaves infested to the mean density of thrips Sample size curves were calculated and compared at 10 and 25 levels of precision The sample sizes required for density estimation at both levels of precision differed between methods The difficulties in developing binomial sampling plans are discussed